2020
DOI: 10.1111/jpn.13414
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of diets with tannins from Chestnut wood or an extract from Stevia rebaudiana Bertoni and effects on in vitro rumen fermentation, protozoa count and methane production

Abstract: The aim of the trial was to evaluate the effect of dietary additions of Stevia rebaudiana Bertoni extract (SB) and Chestnut wood tannin (CWT) on the in vitro rumen fermentability, protozoal population and methane yield. Both plant products were tested at 3 different levels of inclusion (0.75, 1.50 and 3.00% of incubated dry matter, DM) in a total mixed ration (TMR) for ruminants by using rumen batch culture systems and a rumen inoculum collected from sheep. Total volatile fatty acid concentration, their propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…The protozoal population was reduced (Table 5) and methane production was decreased by supplementing with plant materials with high CT and TP concentrations in the fermentation substrate (Table 6). This finding was consistent with those of Sarnataro et al [38], who found that adding Stevia rebaudiana Bertoni extract and chestnut wood tannin to the rumen reduced the in vitro protozoal population while having no effect on the fermentation parameters; whereas Jayanegara et al [39] found dietary tannins had no effect on protozoal numbers in an in vitro study. Newbold et al [40] recommended complete rumen protozoal elimination as a means to increase microbial protein supply by 30% while reducing methane production by up to 11%.…”
Section: In Vitro Rumen Fermentation Bacteria and Protozoal Population Characteristicssupporting
confidence: 89%
“…The protozoal population was reduced (Table 5) and methane production was decreased by supplementing with plant materials with high CT and TP concentrations in the fermentation substrate (Table 6). This finding was consistent with those of Sarnataro et al [38], who found that adding Stevia rebaudiana Bertoni extract and chestnut wood tannin to the rumen reduced the in vitro protozoal population while having no effect on the fermentation parameters; whereas Jayanegara et al [39] found dietary tannins had no effect on protozoal numbers in an in vitro study. Newbold et al [40] recommended complete rumen protozoal elimination as a means to increase microbial protein supply by 30% while reducing methane production by up to 11%.…”
Section: In Vitro Rumen Fermentation Bacteria and Protozoal Population Characteristicssupporting
confidence: 89%
“…(2014) concluded that methanogenesis is also regulated by other mechanisms besides protozoa numbers because, in several experiments, a variation in CH 4 emission was observed without corresponding changes in the protozoa numbers. In addition, Sarnataro et al. (2020) changed the concentration of the in vitro protozoa population by adding secondary plant compounds; however, the authors did not measure a variation in the CH 4 yield.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that a sufficiently numerous and metabolically active protozoa population could be maintained, we chose a short time frame of 24 h to test different protozoa counts in terms of AFs degradation. In previous experiments, it was observed that some natural substances change the in vitro protozoa counts (Sarnataro et al, 2020; Sarnataro & Spanghero, 2020). Specifically, Stevia leaf extract was responsible for a reduction of approximately 50% after 24 h of fermentation using the same in vitro apparatus and dosage as in the current study (Sarnataro & Spanghero, 2020).…”
Section: Discussionmentioning
confidence: 95%